Synthesis of a stimuli-sensitive PEGylated nanoniosomal doxorubicin for the treatment of acute myeloid leukemia: An in vitro study - Fatemeh Bahrami-Banan; Mohammad Hasan Sheikhha; Nasrin Ghasemi; Masoumeh Rahmani; Mahdie Hemati; Mohammadreza Safdari; Fatemeh Haghiralsadat (Nanomedicine Journal, 2023)
Objective(s): One of the effective strategies for targeted chemotherapy of cancer is the use of lipid nanocarriers. In this study, an optimal formulation of niosomal drug containing doxorubicin was developed to monitor the potency against cancer cells. Materials and Methods: In this experimental study, niosomal vesicles were prepared using phosphatidylcholine (20%), span60 (52.5%), cholesterol (22.5%), and DSPE-PEG2000 (5%) by the thin-film method. Doxorubicin was loaded into the niosomes using an inactive loading method. Results: The features and characteristics of the nanocarrier were evaluated using Zeta-Sizer, SEM, FTIR, drug release, cellular uptake, and the cytotoxicity of the nanodrug carrier system by the MTT method. Niosomal vesicles-containing doxorubicin showed a size of ~156.8 nm, drug encapsulation efficiency of ~94.18%, zeta potential of ~-3.52 mV, and polydispersity index (PDI) of ~0.265. The prepared niosomes indicated a drug-controlled release system and FTIR analysis showed no interaction between nanocarriers containing drug and doxorubicin. Moreover, morphological examination of nanocarriers using SEM microscopy revealed that they had spherical structures. Also, cellular studies showed that drug toxicity was higher in encapsulated form of the drug compared with non-encapsulated doxorubicin which was confirmed by the cellular uptake results. Conclusion: The results confirmed the proper physicochemical characteristics of these nanocarriers that significantly increased the toxicity of the encapsulated drug against the KG-1 cell line. It seems niosomal nanocarriers can be considered suitable carriers for drug delivery to cancer cells.